Friday

August 22, 2014

August 22, 2014

Posted by **kristie** on Tuesday, July 11, 2006 at 10:04am.

ln(y-1)-ln2 = x +lnx

ln(y-1)-ln2 = x +lnx Solve for y...

ln[(y-1)/2]]=x + lnx

take the antilog of each side

(y-1)/2= e^(x+lnx)

solve for y.

**Related Questions**

math - I am suppose to simplify the following problems: sqrt(x)/x (isn't that ...

calculus - (a) find the intervals on which f is incrs or decrs. (b) find the ...

L'Hopital's rule - Find lim x->1+ of [(1/(x-1))-(1/lnx)]. Here is my work...

calculus - sorry to ask a second question so soon, but i'm just not getting this...

Calculus 1 - Find the derivative of y with respect to x. y=(x^6/6)(lnx)-(x^6/36...

Math (Calculus) - Can somebody solve this logarithm problem step by step for me ...

calc - integral of 1 to e^4 dx/x(1+lnx) 1+lnx = a => dx/x = da dx/ x(1+lnx...

pre calc - lnX + ln2 = 3

pre calc - lnX + ln2 = 3

Math logs - Solve the system of equations: y= (lnx)^2 + 2 (lnx^2) y = 3ln(1/x^2...